Water Quality Control System and Automatic Feeding Based on The Internet of Things for GoldFish - Mashuri, Mashuri; Sabilaa, Annisa; Mursid, Mashirul; Anandaa, Fanoki Natri; Widiono, Eddy; Sampurnoa, Bambang (IPTEK The Journal of Engineering, 2024)
Water quality affects fish survival and growth. Research on water quality management of aquaculture ponds can improve fish growth. Physical parameters of water quality, such as temperature, acidity, total dissolved solids and turbidity, affect fish growth. Feeding is also important, as fish require adequate feed intake. Improper use of feed can affect water quality indicators. Automatic water quality control and feeding systems have been developed with wireless technology and sensors of various functions. Data sent to mobile devices allows administrators to monitor air quality in fish farms. The creation of an automatic water metering device controlled through a smartphone was also carried out. This research aims to create an automatic water quality stabilization and feeding system for good fish growth.